ALGORITMA MASIH MUSLIATUN (MM) UNTUK MENDUKUNG SISTEM OTOMATISASI PENDAFTARAN PRAKTIKUM DENGAN PENGUJIAN PADA JARINGAN KOMPUTER (STUDI KASUS DI STTA YOGYAKARTA) - Musliatun, Masih; Sajati, Haruno; Indrianingsih, Yuliani (Compiler, 2013)
Practicum registration systems that exist on campus STTA previously done manually, where students will sign up to the admin to bring proof of payment practicum. Students are free to choose his own class, this often resulted in unbalanced number of students in the classroom lab that is consideredless  effective way. This makes the emergence of the idea to establish an MM algorithm is applied to a practical application o f automation systems. MM algorithm works by determining many lab classes based on students who took the KRS. Furthermore, students who have paid practicum will be immediately incorporated into the classes that are available with regard to the number of students and GPA o f students per class, so it will obtain practical classes by the number o f students and the average GPA o f each class balanced.Concept application using client-server database, where the database is on the Local Area Network (LAN) STTA. To facilitate the management admin, then the application will be tested on the LAN network and VPN (Virtual Private Network) network. LAN is a computers network that are connected to a computer server by using specific topologies, typically used in areas of the building or area a distance o f not more than 1 km (local area). While VPN is a secure way to access the Local Area Network that is in range, using the Internet or other public network to perform packet data transmission in private. By using a VPN, users can access the computer that is on the LAN even though the user is not in the same location with a LAN.